Pembinaan Kesemaptaan di UPT SPF SD Negeri 107405 Sei Rotan sebagai Upaya Membentuk Disiplin dan Ketahanan Fisik Peserta Didik - Zamaluddin Sembiring; Rizky Seni Utami (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to analyze the role of fitness development in shaping the discipline and physical resilience of students at UPT SPF SD Negeri 107405 Sei Rotan. The research is motivated by the importance of holistic character education at the elementary level, where fitness does not only focus on physical fitness, but mental formation and discipline. This research uses a qualitative approach with a case study design, involving observation, interviews, and documentation. The results showed that structured activities, such as morning gymnastics, flag ceremonies, and scouting, succeeded in integrating the values of discipline, physical and mental resilience contextually. Students not only become fitter, but also show improvements in time discipline, cooperation, and resilience to challenges. This finding is strengthened by the testimony of teachers stating that routine habituation in the classroom creates a school culture that is conducive to character development. This study recommends the development of more creative and collaborative wellness programs involving parents and the community. The implications of this research provide a practical contribution to strengthening character education in elementary schools through a close approach.